Peran Peternakan Ayam Ras Petelur dalam Meningkatkan Perekonomian pada Masyarakat Desa Pucung Lor Kecamatan Ngantru Kabupaten Tulungagung - Fatma Tri Agustin; Muhammad Alhada Faudilah Habib (Departement of Mathematics Education, 2023)
From the existence of several laying chicken farms in Pucung Lor Village, Ngantru District, it is hoped that it will play a role in improving the economy of the local village community. This study aims to reveal what roles these farms play in improving the economy of the Pucung Lor village community. The method used is descriptive qualitative. This research focuses on the role given by livestock to improve the economy of the local village community. The data used are primary data and secondary data. Data collection techniques were carried out in the field using observation techniques by conducting interviews regarding from an economic perspective what kind of benefits have been obtained from the existence of these farms, then the data was compressed and translated. In improving the economy, livestock provide a role as a provider of employment, increase community income, support the development of local community entrepreneurs. Apart from having a role in the development of the local village economy, these laying hen farms also continue to update their innovations, especially in the field of technology to support the progress of their livestock business and carry out social activities to support community welfare.